PENGARUH E-SERVICE QUALITY, E-TRUST DAN PERCEIVE VALUE TERHADAP KEPUASAN KONSUMEN KARTU PRAKERJA - Ainani Khalishah; Hairani Tarigan (PT Naureen Digital Education, 2023)
This study aims to determine the effect of e-service quality, e-trust and perceived value on customer satisfaction. The population is consumers who have purchased training through the Pre-Employment Card website. The method used is quantitative, the sampling technique in this study uses Nonprobability sampling technique, the method used is purposive sampling. This study used 150 respondents. The method used when testing using the Structural Equation Model (SEM) with the help of Smart-PLS 3.2.9 software. The results of this study state that electronic service quality has a significant effect on customer satisfaction. E-trust has a significant effect on customer satisfaction. Meanwhile, Perceived value also has a significant impact on customer satisfaction